Estimation of crop evapotranspiration using lysimeter / Siti Amni Ismail and Tsan Fui Ying - Ismail, Siti Amni; Tsan, Fui Ying (Research Management Institute (RMI), 2012)
The determination of crop evapotranspiration is important in determining irrigation water requirements in order to have better irrigation management and scheduling. A research was carried out to estimate water requirement (evapotranspiration) for Kacip Fatimah and Stevia Rebaudiana using lysimeter. Three water tables of 15 cm, 25 cm and 30 cm were evaluated. The water table was constant throughout the research and their losses were measured and replaced. The measured water loss is known as the estimated crop water requirement or evapotranspiration (ET). From the result, the water table was significantly affecting the water requirement and growth performance of both crops. For Kacip Fatimah, the average value of ET for water table at 15 cm, 25 cm and 30 cm were at 1.70 mm/day, 1.18 mm/day and 0.48 mm/day respectively. While for Stevia Rebaudiana, the average values of ET were at 1.78 mm/day, 1.58 mm/day and 1.15mm/day respectively. From the analyses of variance, there was a significant difference between plant growth in different water tables as plant height and the length of root were increased as the depth of water table increased. On the other hand, number of leaves were decreased as the depth of water table increased.